1997
DOI: 10.1161/01.cir.96.4.1130
|View full text |Cite
|
Sign up to set email alerts
|

Profound and Sustained Inhibition of Platelet Aggregation by Fradafiban, a Nonpeptide Platelet Glycoprotein IIb/IIIa Antagonist, and Its Orally Active Prodrug, Lefradafiban, in Men

Abstract: Oral administration of Lefradafiban maintains the potent platelet GP IIb/IIIa antagonism of Fradafiban during treatment of healthy subjects for 1 week without signs of loss of the antiplatelet activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 29 publications
1
41
0
1
Order By: Relevance
“…24 Ultimately, it would be presumed that a rapid acting intravenous agent would be administered acutely during the hospitalization for the acute coronary syndrome or revascularization procedure, with outpatient conversion to an orally active preparation of the same compound; indeed, several such products are in development. 25 However, it has been shown that the pharmacodynamic response to an oral GP IIb/IIIa receptor antagonist is potentiated by antecedent treatment with abciximab. 26 Whether this finding will be observed with other combinations of oral and parenteral GP IIb/IIIa receptor antagonists is unknown.…”
Section: Safetymentioning
confidence: 99%
“…24 Ultimately, it would be presumed that a rapid acting intravenous agent would be administered acutely during the hospitalization for the acute coronary syndrome or revascularization procedure, with outpatient conversion to an orally active preparation of the same compound; indeed, several such products are in development. 25 However, it has been shown that the pharmacodynamic response to an oral GP IIb/IIIa receptor antagonist is potentiated by antecedent treatment with abciximab. 26 Whether this finding will be observed with other combinations of oral and parenteral GP IIb/IIIa receptor antagonists is unknown.…”
Section: Safetymentioning
confidence: 99%
“…In this case, even a long-term medication with the antiplatelet agents ASA and ticlopidine was not able to reduce the increased platelet activation sufficiently. A potential therapeutic alternative for this group of patients could be the new generation of orally available synthetic antiplatelet agents, which bind to the platelet glycoprotein receptor IIb/IIIa by mimicking the RGD-sequence of the ligand fibrinogen [44][45][46]. This alternative concept of a long term antithrombotic therapy awaits evaluation in large clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Boehringer Ingelheim [19] tive [17±22] ). The underlying design principles for all these compounds are quite similar.…”
Section: Fradafibanmentioning
confidence: 99%